2019
DOI: 10.4049/jimmunol.1801117
|View full text |Cite
|
Sign up to set email alerts
|

IL-22–Independent Protection from Colitis in the Absence of Nkx2.3 Transcription Factor in Mice

Abstract: The transcription factor Nkx2.3 regulates the vascular specification of Peyer patches in mice through determining endothelial addressin preference and may function as a susceptibility factor in inflammatory bowel diseases in humans. We wished to analyze the role of Nkx2.3 in colonic solitary intestinal lymphoid tissue composition and in colitis pathogenesis. We studied the colonic solitary intestinal lymphoid tissue of Nkx2.3-deficient mice with immunofluorescence and flow cytometry. Colitis was induced in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In humans, the potential pathogenic role of the Nkx2-3 transcription factor was found in inflammatory bowel diseases (Crohn’s and ulcerative colitis) so far [ 23 , 24 ] and also suggested in spondylarthritis more recently [ 32 ]. In mice, the absence of Nkx2-3 proved to be protective in DSS-induced colitis through an IL-22-independent mechanism [ 18 ]. To our knowledge, this was the first experiment where the Nkx2-3 −/− mutation was investigated in the context of autoimmune arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the potential pathogenic role of the Nkx2-3 transcription factor was found in inflammatory bowel diseases (Crohn’s and ulcerative colitis) so far [ 23 , 24 ] and also suggested in spondylarthritis more recently [ 32 ]. In mice, the absence of Nkx2-3 proved to be protective in DSS-induced colitis through an IL-22-independent mechanism [ 18 ]. To our knowledge, this was the first experiment where the Nkx2-3 −/− mutation was investigated in the context of autoimmune arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Along with its role in the development of intestinal lymphoid tissues. Nkx2-3 is crucial for the expression and regulation of the mucosal addressin cell adhesion molecule-1 (MADCAM-1) on the spleen sinus lining cells and on high endothelial venules of the mesenteric lymph nodes and Peyer’s patches [ 17 , 18 , 19 , 20 ]. Nkx2-3 has an important role in spleen organization and function, since it controls the correct micro-environment for B cell maturation and T-cell-dependent (TD) immune reaction [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, IBD (especially Crohn's disease) and AS share more risk alleles with each other than with other related autoimmune diseases, such as RA or coeliac disease 36,64 . Closer examination of the genetic risk factors for Crohn's disease and AS reveals certain factors to be shared, such as genes related to type 3 immunity and epithelial barrier integrity [65][66][67] (Fig. 2).…”
Section: Spa Is a Genetically Driven Diseasementioning
confidence: 99%
“…Although the absence of Nkx2-3 causes transcriptional blockade of MAdCAM-1 expression ( 8 , 14 ), our previous studies indicated that the distribution of colonic lamina propria ILC3s in young adult mice are differentially affected in the lack of Nkx2-3 compared to the absence of MAdCAM-1 itself, so in Nkx2-3 −/− mice the colonic ILC3 number was higher, whereas in MAdCAM-1 −/− mice ILC3 numbers were significantly less ( 20 ). In this work first we sought to determine how these two different forms of MAdCAM-1 deficiency affect the postnatal population kinetics of ILC3s along the entire intestinal tract.…”
Section: Resultsmentioning
confidence: 99%